Clinical and Experimental Medicine - Dammacco, Francesco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Clinical and Experimental Medicine (CLEM) is a multidisciplinary journal that aims to be a forum of scientific excellence and information exchange in relation to the basic and clinical features of the following fields: hematology, onco-hematology, oncology, virology, immunology, and rheumatology. The journal publishes reviews and editorials, experimental and preclinical studies, translational research, prospectively designed clinical trials, and epidemiological studies. Papers containing new clinical or experimental data that are likely to contribute to changes in clinical practice or the way in which a disease is thought about will be given priority due to their immediate importance. Case reports will be accepted on an exceptional basis only, and their submission is discouraged. The major criteria for publication are clarity, scientific soundness, and advances in knowledge. Following submission via the Springer Nature Article Processing Platform (SNAPP), articles are peer-reviewed (under single blind peer review process) and, if accepted, are rapidly published, resulting in immediate international exposure through PubMed/MEDLINE indexing. Clinical and Experimental Medicine has become a fully open access (OA) journal as of January 2024. This means that we will only be publishing articles as Open Access meaning content will be and freely available to readers worldwide, enabling the widest possible dissemination and reuse. This journal also publishes special/guest-edited issues. The peer review process for these articles is the same as the peer review process of the journal in general. Additionally, if the guest editor(s) authors an article in their special issue, they will not handle the peer review process. .
Keywords: Internal medicine; Hematology; Oncology; Internal Medicine; Hematology; Oncology